Identifikasi Pemahaman Sains Mahasiswa PGSD UKSW Tentang Pola Makan Sehari-hari Berbasis Home Science Process Skill - Gamaliel Septian Airlanda (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
The science process skill is important for teachers. However, not all of the student teachers have the competency, experience, and passion to science. The students of PGSD UKSW come from many kinds of background of middle schools that makes them have some different experiences in science competencies. The specific identification is needed to compare their science understanding/ comprehension. Their daily menu (diet) is the proper way to identify the students’ science understanding, because it is an activity that all people have done. The purpose of this research is to identify the students’ science comprehension through daily consumption patterns based on Home Science Process Skill (HSPS), modified from the science process skill steps used at home. HSPS has some advantages, as it makes the student enjoy their science learning and find the basic of knowledge from daily life. The survey methodology was used to find detailed facts about the level of science understanding. The data triangulation were gathered through questionnaires, interviews, and observations, that describe HSPS indicators, consisting of: scrutiny, note down, try out, create, tell (cermati, catat, coba, cipta, cerita). The results showed that 74.07% of the students encounter difficulty especially in the create phase, in which they have to try and create scientific products. It was also found that the highest difficulty was at the the try out and create phase. Thus, the level of student science understanding is still low. The conclusion is an initial stage of an action research to increase every HSPS indicators achievements.